Chics, elegantes e distintas : a moda na Seção Jornal das Famílias da Revista da Semana (1915-1918) - Czrnorski, Sediana Rizzo (2015)
The research aims, based on the analysis of the Journal of Family section, published by Week Magazine from 1915 to 1918, investigate how social distinction concerning the female gender is constructed and spread in the journal. The defined time cutting for this investigation parts based on a modification in the magazine itself, that, up to the 1914, defined itself as a varieties magazine, and, in 1915, began to identify itself as a women's magazine. The final cut is defined by the end of the First World War, event that marked and influenced transformations in fashion. In Brazil, period is marked by the advent of First Republic, and urban reforms, in the context of the emergence of modernity, under European inspiration. The proposed analysis starts from the understanding that fashion has a communicator function, acting as sign system that inform about the roles and / or identities assumed by individuals in their being in the world. It was used as the main source and object of study section Journal of Families of the Week Magazine. The magazine was, at that time, one of the most important publications in that genre, being the pioneer in the use of photography to illustrate their stories and, still, the first major project of a magazine in business lines in Brazil. To understand how images and texts related to fashion in the magazine We are guided by Bourdieu (1989), who understands fashion as a symbolic element of social distinction. We started with the assumption that fashion not only includes clothing, but, likewise, all objects which are related to the composition of appearance, as well as conducts, gestures, values and behaviors, components that will be analyzed as signs of social distinction and gender